The impact of social support on academic motivation levels in higher education - Costa-Lobo, Cristina (2017)
The study presented reveals the procedures, presents and discusses the results of an investigation with the main objective of evaluate the effect of social support on the academic motivation of university students, and to analyze the psychometric characteristics of the scales used. The instruments used in the protocol of investigation are a Sociodemographic Questionnaire, the Multidimensional Scale of Perceived Social Support (MSPSS) and the Motivation to Learn – University students (EMA-U). This study was conducted with a total of 154 students aged 18-29. On the scale of Motivation to Learn - University students, factor analysis allowed the observation of the existence of two factors, the intrinsic motivation and the extrinsic motivation. The area of student training assumed itself as a statistically significant predictor of extrinsic motivation. Regarding intrinsic motivation, we did not observe statistically significant results in the variables present in the study. Regarding social support, we verified, through the factorial analysis, the existence of three factors: Family Social Support; Social Support of Friends, and, Social Support of other significant ones. There is a tendency for high social support results and a concordance between our study and the studied literature regarding factor scores and reliability analysis. Social support in motivation to learn does not behave as a predictor of motivation, both intrinsic and extrinsic, and there is no statistically significant correlation between the two. The results show that social support does not have a significant impact on academic motivation, contrary most of the existing literature.